Microwave Frequency Characterization of Barium Titanate Films Obtained Via Sol-Gel - Marulanda-Bernal, José Ignacio; Gallo-Castrillón, Wilson Henry; Mosquera-Palacio, Diana Marybel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The present work focuses on the structural, morphological and dielectric characterization of barium titanate films (BTO or BaTiO3 due to its chemical formula) deposited by spin coating on crystalline silicon (Si) substrates and CPW resonators using the Sol-Gel technique with a Ba/Ti molar ratio of 0.5/0.5. The coplanar waveguides were manufactured on alumina substrates (Al2O3) with 3 mm of gold (Au) metallization using the laser ablation technique. The scanning electron microscopy (SEM) with X-ray energy dispersion spectrometry (EDS) showed the existence of a BTO film with an elementary composition of 14.62% barium and 5.65% titanium, with a thickness of 0.77 mm measured using the profilometric mode of the atomic force microscopy (AFM). Dielectric characterization was carried out by comparing the frequency response (parameter S21) of a CPW resonator with deposited BTO film and another reference resonator (without film) using a network vector analyzer (VNA). These measurements are compared in turn with computational simulations to obtain the dielectric properties. For the BTO film was determined a relative dielectric constant constant (er) of 160 with a loss tangent (Tand) of 0.012 for a frequency of 3.60 GHz. The dielectric constant constant and the ferroelectric property of the material produced are quite promising for applications in microwave circuits, such as miniaturization and tuning.